Infrasound wave detected on icebreaker SHIRASE - Yoshihiro, Kakinami; Takehiko, Murayama; Masa-yuki, Yamamoto; Masaki, Kanao (2017)
第8回極域科学シンポジウム/横断セッション：[ID] 極域データサイエンス 12月8日（金）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Interdisciplinary sessions: [ID] Polar data science Fri. 8 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object